Purification and Isotype Identification of Glucose Binding Protein in Normal Human Platelets - (:unkn) unknown (My University, 2003)
In this study glucose binding protein was isolated and purified from the normal human platelets and its was determined to identify of isoform. The specific activities of the glucose binding protein in the shock fluid and after Sephadex G-200 and DEAE-Sepharose column chromatographies were found to be 26.4, 37.9, and 84.45 nmolglucose/mg protein, respectively. The molecular weight of glucose binding protein was found to be 29,000 Da by SDS-PAGE. This protein does not correspond to any of the isoforms of the GLUT family described in the literature. After the purification steps, it was determined that platelet glucose binding protein was purified 3.2 times when compared the initial phase.
Keywords: Glucose binding protein; Glucose transporter; Platelet